Transformasi Digital: Pengembangan Aplikasi Kasir untuk Meningkatkan Efisiensi Operasional di Cafe Casa n Co Sub - Seytawardani, Latifah Agustina; Inayah, Sathiul; Basatha, Rizky (Lembaga Yasin AlSys, 2025)
In the context of rapid digitalization, many cafes, including Cafe Casa n Co Sub, face challenges in managing transactions that are still carried out manually, which is at high risk of recording errors and service delays. This research aims to develop a digital cashier application that can improve operational efficiency and recording accuracy in the café. The research method used is a case study with a qualitative approach. This data was collected through in-depth interviews with café owners and staff, direct observation of the operational process, and analysis of related documents. Techniques in data analysis are carried out thematically to identify patterns and provide recommendations for improvement. The results of the study show that the application of information technology in the form of a cashier application can support the management of cafes more professionally and efficiently.